Organizational Culture Evaluation: A Case Study of DPMPTSP Pati Regency - Moch. Ilham Mahendra Putra; M. Irwan Tahir (Pt. Anagata Sembagi Education, 2024)
Problem/Background (GAP): Reviewing the organizational culture of the organizational culture carried out by employees in the implementation of administrative services in the field of investment, licensing, and non-licensing in an integrated manner, with the principles of coordination, integration, synchronization, simplification, security, and legal certainty. Objective: The purpose of this study is to aim to evaluate the performance of workers at the One-Stop Investment and Integrated Service Office (DPMPTSP) of Pati Regency, Central Java Province. Methods: This study used a qualitative approach. A case study on the One-Stop Investment and Integrated Service Office of Pati Regency, which explores the organizational culture at the DPMPTSP of Pati Regency. Result: Based on the results of this study showed: 1) Innovation and Risk Taking have been achieved, it is only necessary to increase innovation in providing services to the community; 2) Attention to detail has been achieved, it needs to be done again by the leader to embrace his subordinates; 3) Orientation to benefits has been successfully achieved; 4) Orientation to people has been successfully achieved; 5) Team orientation has been successfully achieved; 6) Aggressiveness has been achieved; 7) Stability has been successfully achieved, although there are obstacles, namely employees who are still lazy in doing their work. Conclusion: Organizational culture at the Pati Regency Investment and One-Stop Integrated Service Office has been running well, because it meets the indicators of organizational culture. In this study, there are supporting factors and inhibiting factors that have been analyzed through SWOT. Meanwhile, organizational culture strategies have been formulated and partly implemented well and need the latest innovations related to organizational culture strategies.